2021
DOI: 10.1080/02640414.2021.1881280
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual model of sport-specific classification for para-athletes with intellectual impairment

Abstract: The present paper describes the conceptual basis of evidence-based classification of para-athletes with intellectual impairment (II). An extensive description of the theoretical and conceptual foundation of the system as currently conceived is provided, as are examples of its applications in the three sports included in the Paralympic programme for II-athletes in 2020 (i.e., athletics, swimming and table tennis). Evidencebased classification for II-athletes is driven by two central questions: i. How can intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The intellectual ability is the ability in conducting cognitive activity in specific characteristic; (3) Cognitive strategy is the ability in distributing and directing its cognitive activity. This ability consists of concept and principle in problem solving; (4) Motoric ability in the ability in conducting a series of physical movement in coordination until the automatism of physical movement is created (Van Biesen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The intellectual ability is the ability in conducting cognitive activity in specific characteristic; (3) Cognitive strategy is the ability in distributing and directing its cognitive activity. This ability consists of concept and principle in problem solving; (4) Motoric ability in the ability in conducting a series of physical movement in coordination until the automatism of physical movement is created (Van Biesen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Based on all of the above, this paper aimed to: (1) investigate the performance and pacing behaviour differences of people with and without ID during a maximal cycling time trial and (2) explore the influence of a competitive opponent on the cycling performance and pacing behaviour of people with and without ID. Due to the impact of ID on sports performance [6,30], we hypothesise that people without ID will perform better in all cycling trials compared to people with ID. Due to the cognitive nature of pacing [10,31] and the cognitive deficits of people with ID (e.g., decision-making) [7], we expect that people with and without ID will pace themselves differently when they cycle alone (without an opponent).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from taking into account the demands of a sport, it is crucial to consider the specific characteristics related to their cognitive impairment when searching for valid and reliable assessment tools to assess EF in elite athletes with intellectual disability (Van Biesen et al, 2021). It has been demonstrated that the intellectual impairment of people with intellectual disability can interfere with proficiency in certain EF domains, including planning, inhibition, set-shifting, updating and WM (Ball et al, 2008; Lanfranchi et al, 2010; Menghini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%